Uniform rod-like self-assembly of polymer nanofibrils produced via propylene polymerization on Stober silica nuclei supported metallocene catalysts. (June 2019) - Li, Kuo-Tseng; Yang, Cheng-Ni
Graphical abstract: Highlights: Silica nuclei with an open polymeric structure were prepared by Stober method with a surfactant addition. Polypropylene (PP) nanofibrils were produced via propylene polymerization on the silica nuclei. Rod-like self-assembly of PP nanofibrils with uniform size and smooth surfaces was fabricated in a fluid element. The assembly had a width closed to Batchelor microscale proposed in turbulent mixing theory. MAO concentration and catalyst size affected PP weight significantly, but had little effect on PP molecule number. Abstract: Silica nuclei (∼5 nm) and spheres (∼700 nm) were synthesized via Stober method with the addition of a surfactant template, and were used to support Me2 Si(Ind)2 ZrCl2 /MAO for catalyzing propylene polymerization at four different solution MAO concentrations. Self- assembly of polypropylene (PP) nanofibrils was produced with 5 nm catalyst, which had a width close to Batchelor concentration microscale proposed in turbulent mixing theory, and exhibited uniform rod-shape with smooth exterior surfaces. The results suggest that each assembly was formed in a fluid element where propylene diffusion was important, and the smooth exterior surfaces were formed due to the drag action between solvent (toluene) and PP assembly. Inside a fluid element, silica nuclei with an open polymeric structure acted as the template for producing PP nanofibrils, which formed self-assembly via intermolecular force. Polymer yield increased proportionally with the increase of number average molecular weight, indicating that the MAO concentration increase or the catalyst size decrease (from 700 nm to 5 nm) increased propagation rate constant, but had little effect on polymer molecule number (or active site amount) produced.